Isolation and characterization of β-sitosterol from Terminalia arjuna fruit and its growth-promoting effect on beneficial fungi: β-sitosterol from T. arjuna fruit promotes fungal growth - Alikadavath, Shamla; Vijaya Chitra, A.; K. P, Jumaila; Nettoor Veettil, Vajid (Cellular and Molecular Biology, 2025)
Terminalia arjuna, an important medicinal plant in traditional Indian systems, has been extensively studied for its cardioprotective bark. However, limited attention has been given to its fruit, which contains several biologically active phytochemicals with potential antioxidant, anti-inflammatory, and immunomodulatory properties. This study aimed to isolate and partially purify phytoactive compounds from the fruit of T. arjuna using chromatographic techniques, characterize them, and assess their effect on the growth of industrially important fungal strains. Dried and powdered T. arjuna fruit was extracted using 70% methanol. The crude extract was subjected to sequential solvent partitioning followed by column chromatography. The resulting fractions were evaluated using TLC, High Performance Liquid Chromatography (HPLC), and LC-MS for partial purification and confirmation of the phytochemicals. The growth-promoting effect of the purified compound was tested on Trichoderma harzianum by measuring optical density after 48 hours of incubation in the presence of the compound. Methanolic extraction of T.arjuna fruit yielded approximately 1652 mg of dried extract. Column chromatography followed by TLC profiling led to the identification of three pooled fractions (A, B, and C), each with distinct banding patterns and Rf values. Among them, Fraction B exhibited a prominent TLC band at Rf 0.133 and was the most abundant (421 mg). HPLC analysis confirmed the high purity of Fraction B, showing a single dominant peak at retention time 3.113 minutes with an area percentage of 97.8%. In growth promotion assays using Trichoderma harzianum, Fraction B significantly enhanced fungal biomass, with a 32.54% increase in OD600 compared to control. LC-MS analysis in positive ion mode identified a molecular ion at m/z 415 [M+H]+ and a key fragment at m/z 256, consistent with β-sitosterol. The presence of β-sitosterol in fruit of T. arjuna reflects the plant’s long-recognized therapeutic significance and is associated with various beneficial pharmacological effects. This study established that the fruit of T. arjuna can serve as a viable source of β-sitosterol, which may have potential as a natural growth enhancer for industrial fungi.